2011
DOI: 10.1371/journal.pone.0016974
|View full text |Cite
|
Sign up to set email alerts
|

Tea Consumption Enhances Endothelial-Dependent Vasodilation; a Meta-Analysis

Abstract: BackgroundTea consumption is associated with a lower risk of cardiovascular disease including stroke. Direct effects of tea components on the vasculature, particularly the endothelium, may partly explain this association.ObjectiveWe performed a meta-analysis of controlled human intervention studies on the effect of tea on flow-mediated dilation (FMD) of the brachial artery, a measurement of endothelial function, which is suggested to be associated with cardiovascular risk.MethodsHuman intervention studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(100 citation statements)
references
References 62 publications
2
94
4
Order By: Relevance
“…In a meta-analysis of 9 RCTs (2 on green tea, 6 on black tea, and 1 on both types of tea), involving 213 participants, the overall absolute increase in FMD of tea consumption (median daily dose of 500 mL tea, equivalent to 2-3 cups) versus placebo was 2.6% of the arterial diameter. 19 This is a relative improvement of ≈40% compared with the average FMD of 6.3% measured under placebo or baseline conditions. 19 Results from a meta-analysis of 14 short-term (≤3 months) RCTs showed that green tea consumption lowered total and LDL cholesterol concentrations but had no effect on high-density lipoprotein cholesterol.…”
Section: Green and Black Teamentioning
confidence: 85%
“…In a meta-analysis of 9 RCTs (2 on green tea, 6 on black tea, and 1 on both types of tea), involving 213 participants, the overall absolute increase in FMD of tea consumption (median daily dose of 500 mL tea, equivalent to 2-3 cups) versus placebo was 2.6% of the arterial diameter. 19 This is a relative improvement of ≈40% compared with the average FMD of 6.3% measured under placebo or baseline conditions. 19 Results from a meta-analysis of 14 short-term (≤3 months) RCTs showed that green tea consumption lowered total and LDL cholesterol concentrations but had no effect on high-density lipoprotein cholesterol.…”
Section: Green and Black Teamentioning
confidence: 85%
“…These associations remained after adjusting for dietary pattern, suggesting that the 191 oxidative stress and inflammation [29][30][31][32][33] . The strongest beneficial relation with all-cause mortality 195 was observed with the frequency of red wine consumption, which remained even after adjusting 196 for total alcohol consumption, which has been shown to be a strong predictor of all-cause 197 mortality 34 .…”
Section: Discussion 172mentioning
confidence: 96%
“…Each treatment was delivered in six capsules that were consumed in a single sitting. The ingestion of 2,820 mg tea solids is based on the upper intake limit of tea studies looking at vascular effects 5 and was chosen to maximize our chance of seeing an effect of tea on the brain.…”
Section: Methodsmentioning
confidence: 99%
“…3 Flow mediated dilation of the brachial artery is a measure of endothelial function and several intervention studies have shown beneficial effects of tea and other flavonoid-rich foods therein. 4,5 Small doses of flavonoids, equivalent to one cup of tea, already exert a substantial increase in flow mediated dilation. 6 A proposed mechanism is that flavonoids improve the bioavailability of nitric oxide (NO), a key mediator of endotheliumdependent vasodilation, by stimulating activity of endothelial NO synthase or by preventing superoxide-mediated NO breakdown.…”
Section: Introductionmentioning
confidence: 99%